1991
DOI: 10.1016/0248-4900(91)90008-b
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of the epithelial phenotype and functional activity of cultured bovine tracheal gland cells: dependence on the culture medium and passage number

Abstract: Bovine tracheal gland (BTG) cells in culture show an epithelial-fibroblastoid transition after several passages. To investigate these BTG cell phenotype changes, we studied the effects of both the culture medium and passage number on the expression of epithelial cytoskeletal proteins and glandular serous cell markers. We also analyzed the intracellular cAMP level in the basal state and after adrenergic stimulation. Three culture media were used: 1) serum-free defined medium (SFDM); 2) medium supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…used primary VEC that were obtained from enzymatically digested tissue and grown in vitro for at least 2 weeks before treatment. Previous studies have shown that the phenotype of FRT epithelial cells in culture changes with increasing passage number . In contrast, we used freshly isolated VEC that were in culture for a maximum of 72 hrs.…”
Section: Discussionmentioning
confidence: 99%
“…used primary VEC that were obtained from enzymatically digested tissue and grown in vitro for at least 2 weeks before treatment. Previous studies have shown that the phenotype of FRT epithelial cells in culture changes with increasing passage number . In contrast, we used freshly isolated VEC that were in culture for a maximum of 72 hrs.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh bovine tracheae were obtained from a local abattoir. Isolation and culture conditions of bovine tracheal submucosal gland (BTG) [20] and human tracheal submucosal gland (HTG) [21] cells have previously been described.…”
Section: Cell Culturesmentioning
confidence: 99%